Emerging Information and Communication Technologies: the Challenges for the Dynamic Freight Management in City Logistics - Comi, Antonio; Russo, Francesco (Frontiers in Future Transportation, 2022)
Recently, the evolution of emerging information and communication technologies (e-ICT) is opening the road for developing and implementing new integrated and dynamic city logistics solutions, and subsequently for identifying new frontiers of intelligent transport systems (ITS). The paper evolves pointing out the different city logistics groups of actors and their reciprocal interactions in relation to the considered new technologies (i.e., internet of things, block chain, big data and artificial intelligence) which allow actors to increase their utility exploiting the advancement of current intelligent transport systems. The changes in the generalized path costs supported by each stakeholder are explored and the modifications guided by e-ICTs are analyzed. The learning process due to the updating for within-day and day-to-day dynamics were detailed and formalized. In this way, the current formulation of classical transport problem (vehicle routing and scheduling) and the new one (pushed from the growth of ecommerce; i.e., courier routing) are explored under the light of the new knowledge deriving from the use of e-ICT. Novelty of the paper mainly consists of the analysis of each emerging ICT group and of the formalization, in the classical Transport System Models (TSM), of the new knowledge for each actor group.